2010
DOI: 10.1007/s10530-010-9914-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards a global database of weed risk assessments: a test of transferability for the tropics

Abstract: Worldwide spread and establishment of alien plant species continues to accelerate and damage ecological and agricultural systems. Early warning and prevention of high-risk introductions is the most costeffective approach to minimise losses while maximising benefits, and the Australian Weed Risk Assessment (A-WRA) system has been the most well-developed and successful predictive scheme. However, any system would be limited if the results or scores were confined to the locality of assessment. We compiled A-WRA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…The differences in WRA outcomes between our work and earlier assessments (Table 1) contrast with reports of the generality of WRA predictions across geographies with similar climates [39]. Although we sought to conservatively interpret the literature and answered questions only when we found specific evidence, our scores are consistently higher than those from other efforts.…”
Section: Discussioncontrasting
confidence: 78%
“…The differences in WRA outcomes between our work and earlier assessments (Table 1) contrast with reports of the generality of WRA predictions across geographies with similar climates [39]. Although we sought to conservatively interpret the literature and answered questions only when we found specific evidence, our scores are consistently higher than those from other efforts.…”
Section: Discussioncontrasting
confidence: 78%
“…The studies incorporated into Fig. 1 cover a variety of geographic regions, including the United States as a whole, Hawaii and the Pacific Islands, Florida, Italy, and Japan, as previous studies have suggested that Australian WRA evaluations are accurate among regions with similar climates (Gordon et al 2008a, Chong et al 2011.…”
Section: Use Of Wra Tools To Predict Invasion By Biofuel Feedstock Spmentioning
confidence: 99%
“…Davis et al (2010) suggest that secondary screening may be important for species qualifying for accept, as well as evaluate further, in order to reduce the potential for accepting a highly invasive species; their proposed follow-up screens include postintroduction quarantine cultivation trials and monitoring. Two different metastudies have found that the Australian WRA is an effective screening tool across geographic regions (with adaptations for climate matching and the other geography-specific questions highlighted above) and suggest that Australian WRA species evaluations from one location can be used with reasonable confidence for other areas with similar climate (Gordon et al 2008a, Chong et al 2011), although the cross-regional correlation is more accurate for major invaders than minor (Gordon et al 2008a).…”
Section: Use Of Invasiveness Predictors In Pre-introduction Weed Riskmentioning
confidence: 99%
“…There are many risk assessment frameworks (e.g. WRA) that were suggested as reliable systems for global application (Chong et al, 2011). However, most of these assessment frameworks were need specific data, either traits data or other supporting information.…”
Section: Introductionmentioning
confidence: 99%